The Effectiveness of Dipstick for the Detection of Urinary Tract Infection - Isaac Dadzie; Elvis Quansah; Mavis Puopelle Dakorah; Victoria Abiade; Ebenezer Takyi-Amuah; Richmond Adusei (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The balance between the choices of UTI diagnostic tools in most primary care settings has been settled for by the more rapid, less labour-intensive dipstick. This study aimed to evaluate the effectiveness of dipstick for diagnosing UTI. Method. A total of 429 urine samples were collected from patients suspected of UTI; cultured on cysteine-lactose-electrolyte-deficient (CLED) agar, blood agar, and MacConkey agar; and incubated at 37°C overnight. Urine cultures with bacteria count ≥105 cfu/ml were classified as “positive” for UTI. A dipstick was used to screen for the production of nitrite (NIT) and leucocyte esterase (LE), following the manufacturer’s instructions. Biochemical reactions of nitrite and leucocyte esterase > “trace” were classified as “positive.” A quantitative urine culture was used as the gold standard. Results. The highest sensitivity value and negative predictive value were recorded for the combined “NIT+ or LE+” dipstick results. The highest specificity value, positive predictive value, positive likelihood ratio, and negative likelihood ratio were recorded for “nitrite-positive and leucocyte esterase-positive” results. Combined “nitrite-positive or leucocyte-positive” result was relatively the best indicator for accurate dipstick diagnosis, with AUC = 0.7242. Cohen’s kappa values between dipstick diagnosis and quantitative culture were <0.6. Conclusion. Combined performance of nitrite and leucocyte esterase results appeared better than the solo performance of nitrite and leucocyte esterase. However, little confidence should be placed on dipstick diagnosis; hence, request for quantity culture should be encouraged in the primary healthcare settings.